Karakteristik Batupasir Formasi Gumai dan Provenance pada Daerah Muara Pinang, Kabupaten Empat Lawang, Sumatera Selatan - Mifturrahma, Rizkiya; Idarwati, Idarwati (Universitas Batanghari Jambi, 2025)
This study aims to analyze the mineralogical characteristics, texture, structure of sandstone, and examine the origin of the sediments that form the rocks. The methods used in this study include direct observation in the field to determine the characteristics of sandstone starting from color, grain size and texture. Then a microscopic analysis was carried out to identify constituent minerals such as quartz, feldspar and lithics which were then classified using the QFL (Quartz, Feldspar, Lithic fragments) diagram which was then used to determine the origin of the sedimentary material. The results of the provenance analysis show that the sandstone in the Gumai formation contains various mineral compositions. Based on the classification of the tectonic order of the original rocks, the sandstone of the Gumai formation comes from a magmatic arc and recycled orogen.